2015
DOI: 10.2217/fon.15.288
|View full text |Cite
|
Sign up to set email alerts
|

Thoracoscopy in Pleural Effusion – Two Techniques: Awake Single-Access Video-Assisted Thoracic Surgery Versus 2-Ports Video-Assisted Thoracic Surgery Under General Anesthesia

Abstract: Awake single access video-assisted thoracic surgery with local anesthesia improves procedure tolerance, reduces postoperative stay and costs. Materials & methods: Local anesthesia was made with lidocaine and ropivacaine. We realize one 20 mm incision for the 'single-access', and two incisions for the '2-trocars technique'. Results: Mortality rate was 0% in both groups. Postoperative stay: 3dd ± 4 versus 4dd ± 5, mean operative time: 39 min versus 37 min (p < 0.05). Chest tube duration: 2dd ± 5 versus 3dd ± 6. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 10 publications
1
5
0
1
Order By: Relevance
“…The authors found a significant decrease in postoperative complications as well as in many other perioperative outcome measures including quality of life scores and hospital stay. Similar results came from Cajozzo et al (27). Finally in a controlled study from Tacconi et al (40), no substantial difference in morbidity rate was found with either NIVATS or GAVATS decortication for stage II pleural empyemas.…”
Section: High-risk Patientssupporting
confidence: 73%
See 1 more Smart Citation
“…The authors found a significant decrease in postoperative complications as well as in many other perioperative outcome measures including quality of life scores and hospital stay. Similar results came from Cajozzo et al (27). Finally in a controlled study from Tacconi et al (40), no substantial difference in morbidity rate was found with either NIVATS or GAVATS decortication for stage II pleural empyemas.…”
Section: High-risk Patientssupporting
confidence: 73%
“…Other non-randomized studies reported significant differences in hospital stay in the settings of pleural effusion (27,40), pulmonary metastasectomy (42) and secondary PNX (36). On contrary, Wu et al (33) in their study on NIVATS lobectomy in a geriatric population failed to demonstrate any difference in hospital stay length (33).…”
Section: Hospital Staymentioning
confidence: 94%
“…A flow diagram depicting the selection of eligible studies according to the PRISMA guidelines is shown in Figure 1 After the exclusion of 288 studies that did not meet our inclusion criteria, 15 eligible studies (12,15,(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34) were screened out for meta-analyses. One study was published in Chinese, and 14 studies were published in English.…”
Section: Studies Characteristicsmentioning
confidence: 99%
“…Thirteen studies(12,15,22,(24)(25)(26)(27)(28)(29)(31)(32)(33)(34) with complete postoperative complication data were included in the analysis. As the heterogeneity between studies was acceptable (I 2 statistic =23%, P=0.20), the fixed-effect model was adopted for this meta-analysis.…”
mentioning
confidence: 99%
“…VATS daha az ağrı, daha az komplikasyon, daha kısa hastanede kalış süresi ve daha hızlı iyileşme süresi nedeniyle minimal invazif bir cerrahi girişimdir. Bununla birlikte, NI-VATS tekniğinin birçok göğüs cerrahi operasyonunda başarıyla uygulanabileceği mevcut literatürde iyi bilinmektedir (6)(7)(8).…”
Section: Discussionunclassified